Process Mapping and Workload Optimization of Teacher Administrative Tasks: A Service Design and Operations Research Case Study at an International School. - Deb, Priyata (My University, 2026)
Teacher responsibilities in small schools increasingly extend beyond teaching and include a wide range of administrative duties. Teacher burden in terms of stress, time pressure and workload management has been explored in previous studies, but less focus has been placed on the influence of organisational routines and task arrangements on these issues. This thesis explores teacher administrative practices at Norden International School and explores how the school processes and task structures are causing inefficiencies in a small school. The study was based on the systems thinking theory, complemented by service design and lean process improvement. A simple model in Excel with Solver was added as a decision support tool to investigate the potential task allocation options. The study was a pragmatic qualitative case study with three teachers. Structured two-week workload logs, semi-structured interviews and document analysis were used to collect data, which were analysed using process mapping, service blueprinting, workload profiling and root cause analysis. The results indicated that miscommunication, lack of clarity regarding responsibilities, follow-up activities, hidden support activities, duplicated effort and pressure during peak periods were identified as factors contributing to inefficiencies. These challenges were found to be predominantly structural, related to how activities were organised, and not so much to time management per se. This case study suggests that there is a need for better accountability, common monitoring systems, agreed communication procedures, better planning for periods of high demand and careful consideration of suitable activities given out. The results are situation specific, not generalisable conclusions.
Keywords: evaluation; leadership (activity); psychological strain; organisations (systems); workload; systems thinking; work satisfaction; research methods; teachers; decision making; Industrial Systems Analytics; Master's Programme in Industrial Systems Analytics